2017
DOI: 10.1177/1464884917731179
|View full text |Cite
|
Sign up to set email alerts
|

How framing of nationally and locally sensitive issues varies? A content analysis of news from party and nonparty newspapers in China

Abstract: This study investigates how party and nonparty newspapers in China frame sensitive political issues differently, depending on their geographic relevance. Extant studies indicate that political control influences how news organizations present an issue. The assumption is that the framing of nationally sensitive issues is similar across Chinese news outlets, while the framing of locally sensitive issues diverges. An examination of the news frames used by six newspapers in Guangzhou in their coverage of a nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
3
23
0
Order By: Relevance
“…The findings show that party news organizations are more self-censored than the nonparty news organizations as Kuang and Wei (2018) suggest. Indexing (Bennett, 2016) remains a norm for party news media in China, as they set the news agenda and frame news issues in a manner favorable to the political elites.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The findings show that party news organizations are more self-censored than the nonparty news organizations as Kuang and Wei (2018) suggest. Indexing (Bennett, 2016) remains a norm for party news media in China, as they set the news agenda and frame news issues in a manner favorable to the political elites.…”
Section: Discussionmentioning
confidence: 81%
“…Zhang, 2011). In fact, research on the framing of sensitive news in China has suggested that party newspapers are more self-censored than their nonparty counterparts are as they use more leadership frames, which highlight the speeches and actions of political leaders (Kuang & Wei, 2018). Self-censorship is thus one aspect to be studied when comparing the news selection autonomy of Chinese news organizations.…”
Section: Self-censorshipmentioning
confidence: 99%
“…According to existing studies on governmental control in China, the propaganda authorities would request all news organizations in China not to do original reporting on sensitive yet unavoidable issues, such as the Tibet and Taiwan issues, but follow the agenda of the state news agencies like the Xinhua News Agency (Kuang & Wei, 2018; J. Li et al, 2017).…”
Section: Political Control On News Productionmentioning
confidence: 99%
“…In recent years, there have been an increasing number of studies on how political powers influence the frame use of news media (see, for example, Bolsen, 2010; Dimitrova & Kostadinova, 2013; Ferree et al, 2002; Hänggli, 2012; Snow et al, 2007). Good examples include those situated in the Chinese context, among which Luther and Zhou (2005) investigated the news framing of SARS in China and the United States, and Kuang and Wei (2018) looked into the framing of politically sensitive issues which are detrimental to the legitimacy of different levels of government in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation